Kinerja Roda Besi Bersirip Gerak Dengan Mekanisme Sirip Berpegas - Wawan Hermawan (PERTETA, 2010)
Abstract Two sets of movable lug wheel with spring mechanism for hand tractors have been designed and tested. The wheels were set on local hand tractors and tested for tilling paddy fields in Cianjur and Subang districts, West Java. A local fixed lug wheel was also tested in each location. The movable lug wheel for Cianjur location was equipped with a pair of coiled type torsion springs on each lug, while the movable lug wheel for Subang location was equipped with a shaft type torsion spring on each lug. Field performances: theoretical and actual field capacities, wheel slip, and wheel shrinkage, were measured during the test. The test result in Cianjur showed that the movable lug wheel had a better traction performance than the fixed lug wheel. The average wheel slip of the movable lug wheel was 11.54%, while the average wheel slip of the fixed lug wheel was 20.89%. Field efficiency of the movable lug wheel was 76.33%, which was bigger than the fixed lug wheel (68.45%). However, the test result using shaft type torsion springs in Subang showed that the spring mechanism did not work well, and the spring mechanism should be modified on its torsion-shaft diameter and welding strength. Keywords: lug wheel, movable lug, field performance, torsion spring, tillage Diterima: 6 November 2009; Disetujui: 29 Maret 2010